In-hospital mortality and its predictors in a cohort of SLE from Northern India. (December 2020) - Pattanaik, Sarit Sekhar; Muhammed, Hafis; Chatterjee, Rudrarpan; Naveen, R; Lawrence, Able; Agarwal, Vikas; Misra, Durga P; Gupta, Latika; Misra, Ramnath; Aggarwal, Amita
Background: Mortality in SLE has a bimodal peak with early deaths mainly related to disease activity and infection. Although mortality has reduced over years, it is still two to three folds compared to the general population. In India due to increased burden of infection and limited access to health care, the causes may be different. Methods: Retrospective, review of records of all adult SLE patients fulfilling ACR 1997 criteria, who died in hospital between 2000-2019 at a teaching hospital in India was done. In addition, baseline clinical features were extracted for all adult SLE patients seen during this period. Infections were either bacteriologically proven or based on clinicradiological or serologic evidence. Active disease was defined as SLEDAI 2k ≥ 5. Logistic regression was performed to ascertain risk factors for mortality. Results: A total of 1337 (92% females) patient records were reviewed .The mean age at presentation was 29.9 ± 9 years.60–75% of patients had fever, mucocutaneous disease and arthritis, while nephritis, hematologic, serositis and neurologic involvement was seen in 48.6%, 43.2%, 16% and 10.3% respectively as presenting mainfestations. There were 80 in hospital deaths .Infection was the most common cause of death, with 37 due to infection alone and in 24 disease activity also contributed. Only 18 deaths were due to active disease. Among bacterial infections lung was the most common site and gram negative organism were the most common pathogens. There were 10 deaths due to Tuberculosis(TB) and half of them had disseminated disease. Patients with disease activity had a SLEDAI of 14.8 ± 6.4, with neurological, renal and cardiovascular involvement being the major contributors to mortality in 11, 7 and 6 cases respectively. Higher age at onset, male gender, fever, myositis, neurological, cardiovascular, gastrointestinal involvement, vasculitis, elevated serum creatinine at baseline were independent predictors of death. Conclusion: Infections are the most common cause of in-hospital mortality in SLE and TB still accounts for 15% of deaths related to infection. Vasculitis, myositis, cardiovascular and gastrointestinal involvement emerged as novel predictors of mortality in our cohort.